Development of neutron-activated samarium-153-loaded polystyrene microspheres as a potential theranostic agent for hepatic radioembolization. Issue 4 (17th January 2022) - Tan, Hun Yee; Wong, Yin How; Kasbollah, Azahari; Md Shah, Mohammad Nazri; Abdullah, Basri Johan Jeet; Perkins, Alan Christopher; Yeong, Chai Hong
Abstract : Purpose: Hepatic radioembolization is an effective minimally invasive treatment for primary and metastatic liver cancers. Yttrium-90 [ 90 Y]-labelled resin or glass beads are typically used as the radioembolic agent for this treatment; however, these are not readily available in many countries. In this study, novel samarium-153 oxide-loaded polystyrene ([ 153 Sm]Sm2 O3 -PS) microspheres were developed as a potential alternative to 90 Y microspheres for hepatic radioembolization. Methods: The [ 152 Sm]Sm2 O3 -PS microspheres were synthesized using solid-in-oil-in-water solvent evaporation. The microspheres underwent neutron activation using a 1 MW open-pool research reactor to produce radioactive [ 153 Sm]Sm2 O3 -PS microspheres via 152 Sm(n, γ) 153 Sm reaction. Physicochemical characterization, gamma spectroscopy and in-vitro radionuclide retention efficiency were carried out to evaluate the properties and stability of the microspheres before and after neutron activation. Results: The [ 153 Sm]Sm2 O3 -PS microspheres achieved specific activity of 5.04 ± 0.52 GBq·g −1 after a 6 h neutron activation. Scanning electron microscopy and particle size analysis showed that the microspheres remained spherical with an average diameter of 33 μm before and after neutron activation. No long half-life radionuclide and elemental impurities were found in the samples. The radionuclide retention efficiencies of the [ 153 Sm]Sm2 O3 -PS microspheres at 550 h were 99.64 ± 0.07 and 98.76 ± 1.10% when tested in saline solution and human blood plasma, respectively. Conclusions: A neutron-activated [ 153 Sm]Sm2 O3 -PS microsphere formulation was successfully developed for potential application as a theranostic agent for liver radioembolization. The microspheres achieved suitable physical properties for radioembolization and demonstrated high radionuclide retention efficiency in saline solution and human blood plasma.